Proposal for standardizing normal insulin ranges in Brazilian patients and a new classification of metabolic syndrome - Chocair, Pedro Renato; de Menezes Neves, Precil Diego Miranda; Sato, Victor Augusto Hamamoto; Mohrbacher, Sara; Oliveira, Érico Souza; Pereira, Leonardo Victor Barbosa; Bales, Alessandra Martins; da Silva, Fagner Pereira; Duley, John A.; Cuvello-Neto, Américo Lourenço (Frontiers in Medicine, 2022)
Background Insulin resistance and/or hyperinsulinemia are closely linked to adiposity, metabolic syndrome (MetS) and prolonged inflammatory processes. Methods We retrospectively analyzed 1,018 adult individuals with a mean age of 46 years (74% male) and classified them as: Metabolically normal: without any of the five criteria of the International Diabetes Federation (IDF) used for the diagnosis of MetS, plus normal fasting insulin (Men < 8 mU/L, Women < 10 mU/L); Level 1 MetS: with one or two IDF criteria, plus hyperinsulinemia (Men: ≥ 8 mU/L), and Women: ≥ 10 mU/L); Level 2 MetS: with three or more IDF criteria, plus hyperinsulinemia. Results The mean values for fasting insulinemia in metabolically normal individuals was 4.6 ± 1.8 mU/L and 5.6 ± 2.3 mU/L, while their means for the Homeostatic Model Assessment for Insulin Resistance (HOMA-IR) were 1.0 and 1.2 for men and women, respectively. In addition, the mean values for insulin (and HOMA-IR) for individuals with two normal anthropometric parameters (body mass index and waist girth), or two normal anthropometric parameters plus no IDF criteria, were similar to the metabolically normal group. Based on the obtained mean + 2 SD, we established the following insulin (and HOMA-IR) values as diagnostic cut-offs for hyperinsulinemia: Men: ≥ 8 mU/L (≥ 1.5), and Women: ≥ 10 mU/L (≥ 2.0). The mean serum insulin was significantly higher for individuals with Level 1 MetS (approx. 9 mU/L for both genders) compared with metabolically normal individuals, as was the prevalence of hepatic steatosis, which was more evident in men. Thus, the presence of one or two abnormal IDF criteria, combined with hyperinsulinemia and/or raised HOMA-IR, suggests the presence of MetS and insulin resistance. Patients of both genders with Level 2 MetS had higher serum insulin and/or HOMA-IR values than Level 1, as well as a higher prevalence of hypertension and hepatic steatosis, being more pronounced among men. The process was progressive and proportional to the degree of hyperinsulinemia. Conclusion It is proposed that intervention against MetS progression should be started in individuals with Level 1 MetS, rather than waiting for more criteria for diagnostic confirmation, which this should help to reduce the occurrence of known complications such as type 2 diabetes, atherosclerosis, hypertension, and chronic kidney disease, among others.